2016
DOI: 10.1186/s12974-016-0698-0
|View full text |Cite
|
Sign up to set email alerts
|

Astroglia acquires a toxic neuroinflammatory role in response to the cerebrospinal fluid from amyotrophic lateral sclerosis patients

Abstract: BackgroundNon-cell autonomous toxicity is one of the potential mechanisms implicated in the etiopathogenesis of amyotrophic lateral sclerosis (ALS). However, the exact role of glial cells in ALS pathology is yet to be fully understood. In a cellular model recapitulating the pathology of sporadic ALS, we have studied the inflammatory response of astroglia following exposure to the cerebrospinal fluid from ALS patients (ALS-CSF).MethodsVarious inflammatory markers including pro-inflammatory and anti-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 64 publications
4
47
1
Order By: Relevance
“…VEGF delays MN degeneration and increases survival in animal models of ALS [73,74]. In line with these results, low levels of VEGF and GDNF were reported in the CSF of ALS patients [75]. VEGF exerts its antiexcitotoxic effects on MNs through mechanisms involving VEGF receptor-2 and activation of the PI3-K/Akt signaling pathway [72].…”
Section: Neurotrophic Factorssupporting
confidence: 66%
“…VEGF delays MN degeneration and increases survival in animal models of ALS [73,74]. In line with these results, low levels of VEGF and GDNF were reported in the CSF of ALS patients [75]. VEGF exerts its antiexcitotoxic effects on MNs through mechanisms involving VEGF receptor-2 and activation of the PI3-K/Akt signaling pathway [72].…”
Section: Neurotrophic Factorssupporting
confidence: 66%
“…We have earlier reported that ALS-CSF induced apoptosis and reduced ChAT expression in NSC-34 cells [46] with altered neuronal activity and motor de cits in adult rats [47,48]. Conditioned medium from glial cells exposed to ALS-CSF also resulted in reduced viability of NSC-34 cells [31,41]. The reduction in the white matter area observed with staining by phospohorylated neuro laments can be correlated to white matter atrophy observed in ALS patient spinal cord [49].…”
Section: Discussionmentioning
confidence: 96%
“…Microglial proliferation was observed from the pre-clinical stage of disease in mSOD1 rats while hypertrophic GFAP labelled astrocytes were seen only during the late clinical stage [40]. Microglial cells responded prior to astrocytes when exposed to ALS-CSF as microglia showed increased release of pro-in ammatory molecules like interleukin 6, TNF-α and glutamate as early as 12 hours while astrocytes showed a similar response only after 24 or 48 hours [31,41].…”
Section: Discussionmentioning
confidence: 96%
“…Elevated levels of the inflammasome component IL-1 and phosphorylated ERK is also observed in spinal cord astrocytes of ALS mice and patients (Chung et al, 2005;Johann et al, 2015). The secretion of IL-6 by ALS astrocytes can be elicited by the pathogenic pro-inflammatory effector TWEAK (Bowerman et al, 2015), or by the cerebrospinal fluid (CSF) obtained from ALS patients, which in addition to promote TNF production, leads to decreased astrocytic expression of GDNF by astrocytes (Mishra et al, 2016). The decreased ability of SOD1 mutant astrocytes to support motoneuron survival can be ameliorated by GDNF (Das and Svendsen, 2015).…”
Section: Intrinsic Muscle Defectsmentioning
confidence: 99%